KOBRA: a fluctuating elastic rod model for slender biological macromolecules. Issue 32 (24th July 2020) - Welch, Robert; Harris, Sarah A.; Harlen, Oliver G.; Read, Daniel J.
Abstract : KOBRA is a coarse-grained algorithm for parameterising and simulating slender proteins using Kirchoff rods. Abstract : KOBRA (KirchOff Biological Rod Algorithm) is an algorithm and software package designed to perform dynamical simulations of elongated biomolecules such as those containing alpha-helices and coiled-coils. It represents these as coarsely-discretised Kirchoff rods, with linear elements that can stretch, bend and twist independently. These rods can have anisotropic and inhomogeneous parameters and bent or twisted equilibrium structures, allowing for a coarse-grained parameterisation of complex biological structures. Each element is non-inertial and subject to thermal fluctuations. The speed and simplicity of the algorithm allows KOBRA rods to easily access timescales from nanoseconds to seconds. To demonstrate this functionality, a KOBRA rod was parameterised using data from all-atom simulations of the Ndc80 protein complex, and compared against these simulations and negative-stain EM images. The distribution of bend angles and principal components were highly correlated between KOBRA, all-atom molecular dynamics, and experimental data. The properties of a hinge region, thought to be found at an unstructured loop, were studied. A C++ implementation of KOBRA is available under the GNU GPLv3 free software licence.